Methods in cell biology. - Detrich, H. William, III; Westerfield, Monte; Zon, Leonard I. (Methods in cell biology, 2010)
This volume of Methods in Cell Biology, the first of 3 parts on the subject of zebrafish, provides a comprehensive compendia of laboratory protocols and reviews covering all the new methods developed since 2004. This first volume provides state-of-the-art descriptions of novel cellular imaging technologies and methods for culture of zebrafish stem cells, summarizes protocols for analyzingthe development of major organ systems including the central nervous system (CNS), and introduces the use of the zebrafish as a model system for human diseases. * Details state-of-the art zebrafish protocols, delineating critical steps in the procedures as well as potential pitfalls * Summarizes the Zebrafish Genome Project.